1999
DOI: 10.1034/j.1600-0420.1999.770314.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of nonproliferative diabetic retinopathy with Defibrotide in noninsulindependent diabetes mellitus, A pilot study

Abstract: ABSTRACT.Purpose. Microvascular alterations, impairment of coagulation, ischemia and diffuse endothelial damage are related to the progression of diabetic retinopathy. Defibrotide has been demonstrated to produce profibrinolytic, cytoprotective and vasofacilatory activities. The aim of the present study was to evaluate the therapeutic effect of Defibrotide in the treatment of nonproliferative diabetic retinopathy. Methods. Two randomized age-and sex-matched groups (cases and controls) of 35 NIDDM patients pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…If these data were confirmed by other authors, it would be possible not only to reach a better understanding of the pathogenesis of DR but also to prevent its onset and/or progression, helping primary care physicians and ophthalmologists in detecting patients at risk when they can still be treated effectively with conservative methods (for example, drugs with antithrombotic, profibrinolytic, and cytoprotective effects able to restore the endothelial function49) and before the need for laser treatments that always destroy the retinal anatomy.…”
Section: Discussionmentioning
confidence: 68%
“…If these data were confirmed by other authors, it would be possible not only to reach a better understanding of the pathogenesis of DR but also to prevent its onset and/or progression, helping primary care physicians and ophthalmologists in detecting patients at risk when they can still be treated effectively with conservative methods (for example, drugs with antithrombotic, profibrinolytic, and cytoprotective effects able to restore the endothelial function49) and before the need for laser treatments that always destroy the retinal anatomy.…”
Section: Discussionmentioning
confidence: 68%
“…47 Defibrotide also has been investigated in animal and human studies for a wide variety of other conditions, although these data are generally preliminary. Such conditions include acute myocardial infarction 48,49 and coronary reocclusion after thrombolysis in acute myocardial infarction, 50 ischemia and ischemia-reperfusion injury, 6,51-53 ischemic liver damage, 54 diabetic microangiopathy 55 and diabetic retinopathy, 56 Raynaud phenomenon, 57 frostbite, 58 multiple myeloma, 59,60 and malaria. 61 Defibrotide has been most extensively investigated for the treatment and prevention of VOD, also known as SOS, in patients undergoing HSCT 2,62,63 (see "Clinical use of defibrotide in bone marrow transplantation").…”
Section: Key Pharmacologic Actions and Characteristicsmentioning
confidence: 99%
“…Vingolo et al [188] investigated 35 patients with type 2 diabetes mellitus who had nonproliferative retinopathy and who took defibrotide for two years. The authors concluded that ophthalmologic parameters of retinal function were significantly better in the group treated with defibrotide.…”
Section: B) Small Noncontrolled Studiesmentioning
confidence: 99%